Composite gel electrolyte as well as preparation method and application thereof
By using PEO-PAN blended polymer matrix and mesoporous SiO2 nanosphere filler in gel electrolytes, combined with lithium salt, the problems of insufficient ionic conductivity and insufficient mechanical strength of electrolytes in lithium-ion batteries are solved, and higher electrochemical performance and safety are achieved.
Patent Information
- Application Number
- CN202411913469.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing gel electrolytes have problems such as insufficient ion conductivity, prominent interface stability problems, insufficient mechanical strength, complex process and high cost in lithium-ion batteries, which limit their application in high-performance lithium-ion batteries.
The PEO-PAN blended polymer is used as the matrix of the gel electrolyte, and mesoporous SiO2 nanospheres are introduced as reinforcement filler. Combined with appropriate lithium salts, mesoporous SiO2 nanospheres are prepared by template method to optimize the preparation method of composite gel electrolyte.
It improves the ion conductivity, mechanical strength and thermal stability of the electrolyte, reduces the crystallinity of PEO, broadens the electrochemical window, and improves the safety and circulation performance of the battery.
Smart Images

Figure CN119725712A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite gel electrolyte and a preparation method and application thereof. Background Art
[0002] Gel electrolytes have both liquid and solid properties, integrating the high ionic conductivity of liquid electrolytes and the safety advantages of solid electrolytes. The core component of gel electrolytes is the gelling agent, which fixes the liquid electrolyte by constructing a three-dimensional network structure and provides a transmission channel for ions, which not only improves battery safety but also maintains high electrochemical performance. Commonly used gelling agents include polyethylene oxide (PEO), polymethyl methacrylate (PAMM), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF) and its copolymer P (VDF-HFP), hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA). At present, the overall performance of the gelling agent is improved by modifying it to adapt to the continuous development of battery technology.
[0003] The modification technology of gel electrolyte mainly includes blending, copolymerization or cross-linking methods, for example, by introducing inorganic fillers into traditional polymer matrices such as PEO, PAN, PAN, PVDF, etc. or blending with other high molecular polymers to improve ionic conductivity and mechanical properties. In addition, in-situ polymerization and UV curing methods are also used to prepare gel electrolytes with good ionic conductivity and mechanical properties.
[0004] Although modification technology has made some progress in improving the performance of gel electrolytes, there are still some disadvantages, such as insufficient ionic conductivity, prominent interface stability issues, insufficient mechanical strength, complex processes, high costs, etc. Therefore, although gel electrolytes show potential in terms of safety and electrochemical performance, in order to realize their application in high-performance lithium-ion batteries, further research and development is still needed in terms of modification technology, cost control, and process simplification. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0006] To this end, an embodiment of the present invention provides a composite gel electrolyte and a preparation method and application thereof.
[0007] In a first aspect, the present invention provides a composite gel electrolyte, comprising:
[0008] A gelling agent, wherein the mass proportion of the gelling agent in the composite gel electrolyte is 20% to 40%, and the gelling agent comprises PEO and PAN;
[0009] The reinforcing filler accounts for 25% to 35% of the mass of the composite gel electrolyte, and the reinforcing filler includes mesoporous SiO 2 Nanospheres;
[0010] Lithium salts.
[0011] Furthermore, the PEO and the PAN are mixed in equal amounts to form a blended polymer matrix.
[0012] Furthermore, the mesoporous SiO 2 The nanospheres were prepared by template method.
[0013] Furthermore, the mesoporous SiO 2 The specific surface area of nanospheres is 450-550m 2 / g.
[0014] Furthermore, the lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, and lithium bis(oxalatoborate).
[0015] In a second aspect, the present invention provides a method for preparing the composite gel electrolyte provided in the first aspect, comprising the following steps:
[0016] (a) Preparation of mesoporous SiO 2 Nanospheres;
[0017] (b) preparing a PEO-PAN blend polymer matrix;
[0018] (c) Introduction of mesoporous SiO 2 Nanospheres;
[0019] (d) Adding lithium salt.
[0020] Furthermore, the step (a) comprises:
[0021] Dissolving the template in deionized water, adding a silicon source and an acid solution, and stirring to obtain a mixed solution;
[0022] After aging the mixed solution, filtering, washing and drying to obtain a precursor;
[0023] The precursor is calcined to obtain mesoporous SiO 2 Nanospheres.
[0024] Furthermore, the step (b) comprises: adding PEO to a solvent under water bath conditions, stirring until dissolved, adding PAN, and stirring until a transparent flowing colloid is obtained.
[0025] Furthermore, the step (c) comprises: in a water bath, 2The nanospheres are added into the PEO-PAN blend polymer matrix and stirred until uniformly dispersed to obtain a suspension.
[0026] Furthermore, the step (d) comprises: dissolving the lithium salt in a solvent to form an electrolyte, mixing the electrolyte with the suspension, stirring and removing bubbles to obtain a composite gel electrolyte.
[0027] In a third aspect, the present invention proposes the use of the composite gel electrolyte proposed in the first aspect or the composite gel electrolyte prepared by the method proposed in the second aspect in the preparation of a lithium ion battery.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] The present invention uses a PEO-PAN blended polymer as the matrix of the gel electrolyte, combines the high ionic conductivity of PEO with the excellent mechanical properties and electrochemical stability of PAN, improves the ionic conductivity, mechanical strength and thermal stability of the electrolyte, reduces the crystallinity of PEO, broadens the electrochemical window, and improves the safety and cycle performance of the battery.
[0030] The present invention adds mesoporous SiO into the gel electrolyte 2 Nanosphere fillers improve the ionic conductivity, mechanical strength and interface stability of the PEO-PAN blend polymer matrix, while reducing the crystallinity of the polymer, making high-performance lithium-ion batteries safer and more efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0032] Figure 1 The present invention is a flow chart of the preparation method of the composite gel electrolyte;
[0033] Figure 2 The mesoporous SiO prepared in Example 1 of the present invention 2 Electron micrograph of nanospheres. DETAILED DESCRIPTION
[0034] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0035] The composite gel electrolyte, preparation method and application of the present invention are described below with reference to the accompanying drawings.
[0036] The composite gel electrolyte comprises a gelling agent, a reinforcing filler and a lithium salt, wherein in the composite gel electrolyte, the mass proportion of the gelling agent is 20% to 40%, and the mass proportion of the reinforcing filler is 25% to 35%.
[0037] The gelling agent comprises PEO and PAN. The gelling agent comprising both PEO and PAN combines the excellent ionic conductivity of PEO and the outstanding mechanical strength and electrochemical stability of PAN, thereby improving the ionic conductivity, mechanical properties and electrochemical window of the electrolyte, enhancing the safety and cycle stability of the battery, and having good environmental adaptability.
[0038] In some embodiments, PEO and PAN are mixed in equal amounts to form a blended polymer matrix.
[0039] Mesoporous SiO 2 Nanospheres were prepared by template method, and mesoporous SiO 2 The specific surface area of nanospheres is 450-550m 2 / g, the present invention introduces mesoporous SiO 2 Nanospheres act as reinforcing fillers and effectively improve the mechanical strength of gel electrolytes. 2 Nanospheres have a high specific surface area and porous structure, which provide more transmission channels for ions, thereby effectively improving the ion mobility and the ionic conductivity of the electrolyte.
[0040] The present invention optimizes SiO 2 The composite ratio of nanospheres and PEO-PAN blended polymer optimizes the performance of the composite gel electrolyte, obtains a composite gel electrolyte with good fluidity and excellent electrochemical properties, and improves the overall performance and safety of the battery.
[0041] Preparation method of composite gel electrolyte, such as Figure 1 As shown, the following steps are included:
[0042] (a) Preparation of mesoporous SiO 2 Nanospheres;
[0043] (b) preparing a PEO-PAN blend polymer matrix;
[0044] (c) Introduction of mesoporous SiO 2 Nanospheres;
[0045] (d) Adding lithium salt.
[0046] Step (a) comprises: dissolving the template in deionized water, adding a silicon source and an acid solution, and stirring to obtain a mixed solution; aging the mixed solution, filtering, washing, and drying to obtain a precursor; calcining the precursor to obtain a mesoporous SiO 2 Nanospheres.
[0047] The template is P123, and its molecular weight is 5800. It is understandable that the template can also be other suitable types. The silicon source can be ethyl orthosilicate, methyl orthosilicate, sodium silicate, methyltrimethoxysilane, etc.; the acid solution is hydrochloric acid with a concentration of 2 mol / L. The prepared mesoporous SiO 2 The specific surface area of nanospheres is 450-550m 2 / g.
[0048] The step (b) comprises: adding PEO to a solvent under water bath conditions, stirring until dissolved, adding PAN, and stirring until a transparent flowing colloid is obtained, wherein the water bath temperature is 50-70°C.
[0049] The step (c) comprises: in a water bath, 2 The nanospheres are added into the PEO-PAN blend polymer matrix and stirred until uniformly dispersed to obtain a suspension, wherein the water bath temperature is 50-70°C.
[0050] The step (d) comprises: dissolving the lithium salt in a solvent to form an electrolyte, mixing the electrolyte with the suspension, and removing bubbles after stirring to obtain a composite gel electrolyte. The solvent is EC, DMC and DEC in a volume ratio of 1:1:1; and the method of removing bubbles can be ultrasonic oscillation.
[0051] The present invention is described below in conjunction with specific examples. The test materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0052] Example 1
[0053] Preparation of mesoporous SiO 2 Nanospheres:
[0054] Under a water bath condition of 40° C., 15 g of triblock copolymer P123 was dissolved in 800 mL of deionized water to form a uniform solution. P123 is a nonionic surfactant with a molecular weight of 5800.
[0055] 300 g of tetraethyl orthosilicate (TEOS) and 50 mL of 2 mol / L hydrochloric acid (HCl) were added to the above solution, and the mixture was stirred vigorously for 10 h to promote the hydrolysis and condensation of TEOS, and a mixed solution was obtained.
[0056] The mixed solution was placed in a 2L polytetrafluoroethylene liner and aged at 130°C for 6h. Impurities in the reaction solution were removed by filtering and washing, and then the obtained precursor was dried.
[0057] Finally, the template P123 was removed by calcination at 550 °C for 5 h in a muffle furnace to obtain pure SBA-15 mesoporous silica. Figure 2 shown.
[0058] Preparation of PEO-PAN blend polymer matrix:
[0059] Under the condition of heating in a water bath at 60°C, weighed PEO was added to the heated DMAC according to the proportion, and after slowly stirring until PEO was completely dissolved, weighed PAN was added to the solution, and slowly stirred to mix until a uniform and transparent flowing colloid was obtained. The solution concentration was adjusted as needed to make the solid mass fraction 50%, thereby obtaining a PEO-PAN blend.
[0060] Introduction of mesoporous SiO 2 Nanospheres:
[0061] The synthesized mesoporous SiO 2 The nanospheres were added into the PEO-PAN blend, and were evenly dispersed by slow stirring and ultrasonic vibration to obtain a suspension.
[0062] Adding lithium salt:
[0063] Lithium salt (LiPF 6 ) was dissolved in an appropriate solvent (EC+DMC+DEC) to form 1.5M LiPF 6 EC:DMC:DEC (1:1:1) electrolyte was then mixed with the above suspension, mechanically stirred for 2 hours, and then subjected to ultrasonic oscillation treatment for 30 minutes to remove bubbles, thereby obtaining a composite gel electrolyte with a certain flow state.
[0064] The gel electrolyte in this embodiment is composed of mesoporous SiO 2 Nanospheres, LiPF 6 / EC+DMC+DEC electrolyte and PEO-PAN mixed system, in which mesoporous SiO 2 The mass percentage of the nanospheres is 30%, the mass percentage of PAN is 15%, the mass percentage of PEO is 15%, and the mass percentage of the electrolyte is 40%.
[0065] Example 2
[0066] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 25%, the mass percentage of PAN is 15%, the mass percentage of PEO is 15%, and the mass percentage of the electrolyte is 45%.
[0067] Example 3
[0068] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 35%, the mass percentage of PAN is 15%, the mass percentage of PEO is 15%, and the mass percentage of the electrolyte is 35%.
[0069] Example 4
[0070] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 30%, the mass percentage of PAN is 20%, the mass percentage of PEO is 20%, and the mass percentage of the electrolyte is 30%.
[0071] Example 5
[0072] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 30%, the mass percentage of PAN is 10%, the mass percentage of PEO is 10%, and the mass percentage of the electrolyte is 50%.
[0073] Example 6
[0074] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 25%, the mass percentage of PAN is 17.5%, the mass percentage of PEO is 17.5%, and the mass percentage of the electrolyte is 40%.
[0075] Example 7
[0076] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 35%, the mass percentage of PAN is 12.5%, the mass percentage of PEO is 12.5%, and the mass percentage of the electrolyte is 40%.
[0077] Comparative Example 1
[0078] The difference from Example 1 is that the mass percentage of PAN is 20%, the mass percentage of PEO is 20%, the mass percentage of the electrolyte is 60%, and no mesoporous SiO is contained. 2 Nanospheres.
[0079] Comparative Example 2
[0080] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 30%, the mass percentage of PEO is 30%, the mass percentage of the electrolyte is 40%, and PAN is not included.
[0081] Comparative Example 3
[0082] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 30%, the mass percentage of PAN is 30%, the mass percentage of the electrolyte is 40%, and PEO is not included.
[0083] Comparative Example 4
[0084] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 40%, the mass percentage of PAN is 10%, the mass percentage of PEO is 10%, and the mass percentage of the electrolyte is 40%.
[0085] Comparative Example 5
[0086] The difference from Example 1 is that the mesoporous SiO 2 The mass percentage of the nanospheres is 25%, the mass percentage of PAN is 30%, the mass percentage of PEO is 30%, and the mass percentage of the electrolyte is 15%.
[0087] Test Example 1
[0088] The mesoporous SiO prepared in Example 1 2 The nanospheres were tested by SEM, and the test results are as follows Figure 2 As shown. Figure 2 It can be seen that mesoporous SiO 2 The nanospheres are regular and uniform in shape and have good appearance.
[0089] Test Example 2
[0090] The composite gel electrolytes prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were respectively tested for fluidity, thermal stability and ionic conductivity. The composite gel electrolytes prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were respectively assembled with lithium iron phosphate positive electrodes and graphite negative electrodes into semi-solid lithium ion batteries, and the cycle performance of the lithium ion batteries was tested. The test results are shown in Table 1.
[0091] Among them, the fluidity test method is: when the electrolyte container is tilted to an angle of 45°, if the electrolyte is leveled in less than 10 minutes, it indicates that its fluidity is excellent; if the electrolyte is leveled within 10 minutes to 2 hours, its fluidity is medium; if the material cannot form a flowing gel electrolyte, or the electrolyte is leveled only after being tilted at a 45° angle for more than 2 hours, it is considered that the fluidity is poor.
[0092] The thermal stability test method is: place the electrolyte in an oven at 60°C. If the weight loss is less than 10% within 1 hour, it is considered to have excellent thermal stability; if the weight loss is between 10% and 30% within 1 hour, the thermal stability is medium; if the weight loss exceeds 30% within 1 hour, the thermal stability is poor.
[0093] The test method of ionic conductivity is as follows: the ionic conductivity test of the gel electrolyte adopts the AC impedance spectroscopy method, the gel electrolyte is sandwiched between two platinum electrodes at room temperature, an AC voltage of 5mV is applied through the electrochemical workstation, and the impedance response in the frequency range of 1Hz to 100kHz is measured. The ionic conductivity is calculated using the formula σ=L / (R×S), where L is the thickness of the electrolyte, R is the total impedance of the electrolyte, and S is the effective area of the electrode.
[0094] The cyclic performance test method of the semi-solid lithium-ion battery is: charge and discharge capacity test at 0.33C, and record the capacity retention rate after 300 cycles.
[0095] Table 1:
[0096] Grouping Liquidity Thermal stability Ionic conductivity Capacity retention rate after 300 cycles Example 1 excellent excellent 6.55mS / cm 93.5% Example 2 excellent excellent 5.97mS / cm 92.6% Example 3 excellent excellent 6.25mS / cm 93.0% Example 4 medium excellent 5.84mS / cm 92.5% Example 5 excellent excellent 6.46mS / cm 91.8% Example 6 excellent excellent 6.17mS / cm 92.4% Example 7 excellent excellent 5.75mS / cm 91.5% Comparative Example 1 Difference medium 3.58mS / cm 68.5% Comparative Example 2 medium Difference 4.66mS / cm 54.9% Comparative Example 3 medium Difference 4.35mS / cm 53.5% Comparative Example 4 Difference medium 5.03mS / cm 42.7% Comparative Example 5 Difference medium 5.11mS / cm 45.6%
[0097] According to Table 1, we can see that:
[0098] Compared with the comparative example, the gel electrolytes prepared in Examples 1 to 7 have good fluidity and stability as well as higher conductivity and cycle stability.
[0099] According to Example 1 and Comparative Example 1, when no mesoporous SiO 2 When the nanospheres are added, the ionic conductivity of the composite gel electrolyte decreases significantly.
[0100] According to Example 1 and Comparative Examples 2 and 3, when only PAN or only PEO is added, the ionic conductivity of the composite gel electrolyte is significantly reduced, and the cycle performance of the lithium ion battery prepared therefrom is significantly reduced.
[0101] According to Example 1 and Comparative Examples 4 and 5, when the mesoporous SiO 2 When too much nanospheres are added or when too much PAN and PEO are added, the fluidity of the composite gel electrolyte deteriorates and the cycle performance of the lithium-ion battery prepared therefrom is significantly reduced.
[0102] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0103] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0104] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A composite gel electrolyte, characterized in that: include: A gelling agent, wherein the mass proportion of the gelling agent in the composite gel electrolyte is 20% to 40%, and the gelling agent comprises PEO and PAN; A reinforcing filler, wherein the mass proportion of the reinforcing filler in the composite gel electrolyte is 25% to 35%, and the reinforcing filler comprises mesoporous SiO2 nanospheres; Lithium salts.
2. The composite gel electrolyte according to claim 1, characterized in that The PEO and the PAN are mixed in equal amounts to form a blended polymer matrix.
3. The composite gel electrolyte according to claim 1, characterized in that The mesoporous SiO2 nanospheres are prepared by a template method, and the specific surface area of the mesoporous SiO2 nanospheres is 450 to 550 m 2 / g.
4. The composite gel electrolyte according to claim 1, characterized in that The lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, and lithium bis(oxalatoborate).
5. A method for preparing a composite gel electrolyte, characterized in that: The method for preparing the composite gel electrolyte according to any one of claims 1 to 4 comprises the following steps: (a) Preparation of mesoporous SiO2 nanospheres; (b) preparing a PEO-PAN blend polymer matrix; (c) introduction of mesoporous SiO2 nanospheres; (d) Adding lithium salt.
6. The method according to claim 5, characterized in that The step (a) comprises: Dissolving the template in deionized water, adding a silicon source and an acid solution, and stirring to obtain a mixed solution; After aging the mixed solution, filtering, washing and drying to obtain a precursor; The precursor is calcined to obtain mesoporous SiO2 nanospheres.
7. The method according to claim 5, characterized in that The step (b) comprises: adding PEO to a solvent under water bath conditions, stirring until dissolved, adding PAN, and stirring until a transparent flowing colloid is obtained.
8. The method according to claim 5, characterized in that The step (c) comprises: adding the mesoporous SiO2 nanospheres into the PEO-PAN blended polymer matrix under water bath conditions, and stirring until the nanospheres are evenly dispersed to obtain a suspension.
9. The method according to claim 8, characterized in that The step (d) comprises: dissolving the lithium salt in a solvent to form an electrolyte, mixing the electrolyte with the suspension, and removing bubbles after stirring to obtain a composite gel electrolyte.
10. Use of the composite gel electrolyte according to any one of claims 1 to 4 or the composite gel electrolyte prepared by the method according to any one of claims 5 to 9 in the preparation of lithium ion batteries.
Citation Information
Patent Citations
Method for preparing mesoporous silicon oxide microballoons
CN102398907A
Pan-peo gels with improved conductance and solvent retention
CN103069635A
Composite electrolyte for lithium-sulfur battery as well as preparation method and application thereof
CN110931851A
Double-layer porous composite gel polymer electrolyte for lithium-sulfur battery and preparation method of double-layer porous composite gel polymer electrolyte
CN115036561A
Organic-inorganic co-modified PEO solid electrolyte and preparation method thereof
CN117525574A